Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1108/02683940810904402
|View full text |Cite
|
Sign up to set email alerts
|

Learning orientation, organizational commitment and talent retention across generations

Abstract: Purpose -The purpose of this study is to test the relationships of learning, organizational commitment and talent retention across managerial generations in Europe. Design/methodology/approach -Hypotheses are developed to explain the influence of learning and organizational commitment on talent retention across generations. A total of 1,666 European managers completed a survey on these issues. Depending on year of birth, they were categorized into four generational cohorts. Their answers were analyzed with sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
160
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(179 citation statements)
references
References 61 publications
(59 reference statements)
5
160
1
10
Order By: Relevance
“…Furthermore, organizational commitment continues to be valued by organizational leaders (Morrow, 2011) despite the fact that organizations are currently operating in a historical era no longer characterized by long term employment (e.g., Cappelli, 2000). In addition, downsizing and the emergence of a new generation of employees have been identified as possible explanations for lower commitment levels (D'Amato & Herzfeldt, 2008). Literature revew has demonstrated that employees' commitment to the organization has a variety of important organizational consequences.…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…Furthermore, organizational commitment continues to be valued by organizational leaders (Morrow, 2011) despite the fact that organizations are currently operating in a historical era no longer characterized by long term employment (e.g., Cappelli, 2000). In addition, downsizing and the emergence of a new generation of employees have been identified as possible explanations for lower commitment levels (D'Amato & Herzfeldt, 2008). Literature revew has demonstrated that employees' commitment to the organization has a variety of important organizational consequences.…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…Competition among the organizations has increased and talented employee's retention has become the first priority of the organization [9]. Not only organizations confronted of furious competition of products but as well as faced problem of best employee retention [8]. Right retentions strategy made possible for the organizations to survive and grow in the market [10] and complementary for more profit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Organizational operation executed by the talented employees, whose not only achieve the organizational goals and objectives as well as bring satisfaction in their team members [6][7]. The war of best employees retention has been started and organizations made huge investments in this context [8] for competing and leading the market [9]. Right retention strategy required for the growth but slightly errerous strategy hurt the profitability and growth [10] that is why no space for gaffe.…”
Section: Introductionmentioning
confidence: 99%
“…Experience generation X gained during their childhood and adolescence create the need for continuous learning and increasing capabilities and skills. Hence generation specific HR practices are more effective for employee retention (D'Amato and Herzfeldt, 2008;Kupperschmidt, 2000).…”
Section: Salesforce Turnover Intentionsmentioning
confidence: 99%